A(2A) adenosine receptor upregulation correlates with disease activity in patients with systemic lupus erythematosus - Bortoluzzi, Alessandra (Arthritis Res Ther, 2016)
BACKGROUND: Adenosine is a purine nucleoside implicated in the regulation of the innate and adaptive immune systems, acting through its interaction with four cell surface receptors: A(1), A(2A), A(2B), and A(3). There is intense interest in understanding how adenosine functions in health and during disease, but surprisingly little is known about the actual role of adenosine-mediated mechanisms in systemic lupus erythematosus (SLE). With this background, the aim of the present study was to test the hypothesis that dysregulation of A(1), A(2A), A(2B), and A(3) adenosine receptors (ARs) in lymphocytes of patients with SLE may be involved in the pathogenesis of the disease and to examine the correlations between the status of the ARs and the clinical parameters of SLE. METHODS: ARs were analyzed by performing saturation-binding assays, as well as messenger RNA and Western blot analysis, with lymphocytes of patients with SLE in comparison with healthy subjects. We tested the effect of A(2A)AR agonists in the nuclear factor kB (NF-kB) pathway and on the release of interferon (IFN)-α; tumor necrosis factor (TNF)-α; and interleukin (IL)-2, IL-6, IL-1β, and IL-10. RESULTS: In lymphocytes obtained from 80 patients with SLE, A(2A)ARs were upregulated compared with those of 80 age-matched healthy control subjects, while A(1), A(2B), and A(3) ARs were unchanged. A(2A)AR density was inversely correlated with Systemic Lupus Erythematosus Disease Activity Index 2000 score disease activity through time evaluated according to disease course patterns, serositis, hypocomplementemia, and anti-double-stranded DNA positivity. A(2A)AR activation inhibited the NF-kB activation pathway and diminished inflammatory cytokines (IFN-α, TNF-α, IL-2, IL-6, IL-1β), but it potentiated the release of anti-inflammatory IL-10. CONCLUSIONS: These data suggest the involvement of A(2A)ARs in the complex pathogenetic network of SLE, acting as a modulator of the inflammatory process. It could represent a compensatory pathway to better counteract disease activity. A(2A)AR activation significantly reduced the release of proinflammatory cytokines while enhancing those with anti-inflammatory activity, suggesting a potential translational use of A(2A)AR agonists in SLE pharmacological treatment.